Factors Influencing Obesity on School-Aged Children (Faculty of Medicine Universitas Indonesia, 2006)
School-aged children of 6-12 year old in big cities have less physical activities and relax life style. Fast food and soft drink consumed contain high calorie and protein of protein and carbohydrate sources. Obesity has impact on childrenâs growth and development especially on psychosocial aspect. The factors that play a role in supporting the obesity occurrence in children include socio-economic condition, behavior and life style and diet. A cross sectional descriptive –analytic study was conducted on elementary school students in Jakarta, to identify factors that play roles on obesity of school-aged children. (Med J Indones 2006; 15:43-54) Keywords: childhood obesity, weight shape index, body mass index